Analisa Ukuran Butiran Sedimen Pantai Desa Aeng Kabupaten Takalar dan Pantai Padongko Kabupaten Barru - Hasdinar Umar; Taufiqur Rachman; Sabaruddin Rahman; Chairul Paotonan; Achmad Yasir Baeda; Taufiqurrahman Taufiqurrahman; Ilham Alkhaer (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
Beach is an area that is physically subject to change. This change is caused by natural processes and human activities. Physical changes that generally occur on the beach are erosion and sedimentation. The dynamic processes that occur atthe beach are the result of a combination of various forces at work on the beach, which include the force of waves,currents, sedimentary movements, wind and so on. To analyze sediment transport in coastal areas, one of the main thingsthat need to be known is the characteristics of coastal sediments. The study was carried out on beaches prone to erosion and sedimentation, the location of sample data research at several points taken in the area around the Aeng TakalarVillage Beach and Padongko Barru Beach. The analysis carried out is the analysis of the distribution of sediment grainsto determine the characteristics of existing sediments on the beach. The results showed that the sizes of the sediment samples on the beach in Aeng Village, Takalar District were a mixture of fine sand and medium sand which had a diameterof 0.125 mm - 0.5 mm and the size of the sediment grains on the Padongko beach. Kabru was a mixture of fine sand and medium sand which has a diameter of 0.125 - 0.5 mm.